1982
DOI: 10.1136/jech.36.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in childhood eczema.

Abstract: SUMMARY The cumulative rate of childhood eczema during the first three years was studied in a birth cohort of 1265 New Zealand infants. A parental history of eczema was the strongest predictor of rates of childhood eczema but parental asthma was also related to childhood eczema. Children exposed to an early diverse solid-food diet also had increased risks of eczema, but there was no evidence to suggest that breast-feeding practices had any effect on rates of eczema. Analysis of the data suggested that the appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

1983
1983
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 10 publications
2
50
1
Order By: Relevance
“…Of the eight studies reporting positive benefits, five2-5 8 were based on samples of children chosen for a clear history of parental atopy, one study6 was based on a general population sample in which children of atopic parentage were thought to be over-represented, and only two' 7 were based on population samples. In contrast, of the six studies (including the present study) which have found no benefits, five9-11 13 have been based on population samples and one12 on a case control design. This correlation between methods of sample selection and reports of benefits for breast feeding strongly suggests that a correlation between breast feeding and reduced risks of atopic disease may exist only for children with a clear and perhaps severe family history of atopy.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Of the eight studies reporting positive benefits, five2-5 8 were based on samples of children chosen for a clear history of parental atopy, one study6 was based on a general population sample in which children of atopic parentage were thought to be over-represented, and only two' 7 were based on population samples. In contrast, of the six studies (including the present study) which have found no benefits, five9-11 13 have been based on population samples and one12 on a case control design. This correlation between methods of sample selection and reports of benefits for breast feeding strongly suggests that a correlation between breast feeding and reduced risks of atopic disease may exist only for children with a clear and perhaps severe family history of atopy.…”
Section: Discussioncontrasting
confidence: 56%
“…The method of data collection has been described in previous papers." 13 The following measures were chosen for analysis:…”
Section: Methodsmentioning
confidence: 99%
“…A recent review 4 identified only a few studies with conflicting results on the relationship between early introduction of solids and the development of allergic disease. [5][6][7][8][9][10] We recently published results of the Influences of Lifestyle-Related Factors on the Immune System and the Development of Allergies in Childhood (LISA) study, a large, prospective, population-based birth cohort study on asthma and allergic disease. 11 In this cohort, there was no clear evidence of a protective effect of a delayed introduction of solids (past 4 or 6 months) on the development of eczema or sensitization at 2 years of age; however, asthma and allergic rhinitis were not investigated because these conditions play a minor role and diagnosis is difficult at this age.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the Danish study by Shultz-Larsen et al involving atopic twins found that among monozygotic twins there was 85% concordance compared with 21% for dizygotic twins. Fergusson et al 26 interviewed the mothers of a birth cohort of 1265 infants delivered in maternity units in an urban region in New Zealand, supplemented by diaries kept by the mothers and by attendance records for the community nurse. This study found that the perinatal risk of atopic eczema was almost double for those children with a parental history of eczema compared with those with no parental history.…”
Section: Epidemiology Of Childhood Atopic Eczemamentioning
confidence: 99%